2006
DOI: 10.1002/cii.22
|View full text |Cite
|
Sign up to set email alerts
|

Language and theory-of-mind development in prelingually deafened children with cochlear implants: a preliminary investigation

Abstract: One cognitive domain in which deaf children are known to lag behind their hearing peers is that of ‘theory of mind’. Impoverished early conversational experience and deprivation of discussion about intangible mental states are seen as likely contributors to this deficit. The present study explored the relation between language and theory‐of‐mind capabilities in prelingually deafened children aged 4 to 11 years who were cochlear implant users. The children completed theory‐of‐mind tasks that indexed their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There are equally strong support mechanisms for families who choose sign language as a mode of communication and those who prefer to use spoken language via initiatives such as the family sign curriculum or auditory verbal therapy. As confidence grows in developing shared language competence with deaf children, there is a need to be mindful of the part that those around the child play in developing social cognition (Ketelaar, Rieffe, Wiefferink, & Frijns, 2012; Macaulay, 2006; Remmel & Peters, 2009) and the uncertainties and challenges this may bring.…”
Section: Resultsmentioning
confidence: 99%
“…There are equally strong support mechanisms for families who choose sign language as a mode of communication and those who prefer to use spoken language via initiatives such as the family sign curriculum or auditory verbal therapy. As confidence grows in developing shared language competence with deaf children, there is a need to be mindful of the part that those around the child play in developing social cognition (Ketelaar, Rieffe, Wiefferink, & Frijns, 2012; Macaulay, 2006; Remmel & Peters, 2009) and the uncertainties and challenges this may bring.…”
Section: Resultsmentioning
confidence: 99%
“…Results reveal that orally-communicating and late-signing children are delayed not just on standard false-belief tasks but in understanding mental states in general. It has been suggested that the reason for the difficulties in understanding ToM exhibited by these children is related to their limited participation in high quality social interactions involving mental discourse, in their family or educational setting (Jeanes, Nienhuys, & Rickards, 2000;Macaulay & Ford, 2006;Preisler, Tvingstedt, & Ahlstrom, 2002).…”
Section: Development Of Tom Among Deaf Childrenmentioning
confidence: 99%